Relationship between Service Quality and Customer Satisfaction in Hotel Industry - Sharma, Savita; Srivastava, Sidharth (Institut Pariwisata Trisakti, 2018)
In the competitive hotel industry, individual hotels find ways to be unique to make their products and services shine amongst others. Hotels do not leave any stone unturned to deliver best of the services to magnetize the customers. Therefore, the purpose of this review paper is to study whether high level of quality service actually leads to satisfied customers and makes them loyal towards a particular hotel brand. Further, the study intends to explore whether SERVQUAL model is applicable for the hotels to satisfy their customers. Papers related to service quality and customer satisfaction were reviewed from the online database. This paper contributes to the existing literature to explore the relationship between service quality and customer satisfaction and suggests that SERVQUAL method can be applied to the hotel industry to measure the customer satisfaction on the basis of five factors known as assurance, empathy, reliability, and tangibility, which will further lead the hoteliers to improvise customer services